1996
DOI: 10.1021/jp9606974
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Chemical Processing of 13NO2 by Monodisperse Carbon Aerosols at Very Low Concentrations

Abstract: The heterogeneous reaction of NO 2 with different carbon aerosol particles was investigated in situ. The NO 2 was labeled with the + -emitter 13 N (half-life 10.0 min) which allowed application of NO 2 at very low concentrations. The carbon aerosol was either produced by a spark discharge generator using graphite electrodes or by a brush generator resuspending commercial soot material. Monodisperse size cuts between 50-and 490-nm diameter were selected and mixed with the 13 NO 2 . After a defined reaction time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…NO 2 of the order of 10 −2 on soot surfaces (Rogaski et al, 1997;Gerecke et al, 1998). Other studies found uptake rates that were several orders of magnitude lower (Kalberer et al, 1996;Ammann et al, 1998;Longfellow et al, 1999;Al-Abadleh and Grassian, 2000;Kirchner et al, 2000), surface saturation effects that result in a time dependence of the uptake (Ammann et al, 1998;Longfellow et al, 1999;Al-Abadleh and Grassian, 2000;Kirchner et al, 2000) and also a strong dependency on the type of soot used (Kalberer et al, 1996;Kirchner et al, 2000). Recent papers by Kamm et al (1999) and Saathoff et al (2001) show results from a very large aerosol chamber (AIDA, 84 m 3 volume) where spark discharge produced soot particles were used.…”
Section: Chemistry In the Plumementioning
confidence: 94%
See 1 more Smart Citation
“…NO 2 of the order of 10 −2 on soot surfaces (Rogaski et al, 1997;Gerecke et al, 1998). Other studies found uptake rates that were several orders of magnitude lower (Kalberer et al, 1996;Ammann et al, 1998;Longfellow et al, 1999;Al-Abadleh and Grassian, 2000;Kirchner et al, 2000), surface saturation effects that result in a time dependence of the uptake (Ammann et al, 1998;Longfellow et al, 1999;Al-Abadleh and Grassian, 2000;Kirchner et al, 2000) and also a strong dependency on the type of soot used (Kalberer et al, 1996;Kirchner et al, 2000). Recent papers by Kamm et al (1999) and Saathoff et al (2001) show results from a very large aerosol chamber (AIDA, 84 m 3 volume) where spark discharge produced soot particles were used.…”
Section: Chemistry In the Plumementioning
confidence: 94%
“…by converting NO 2 in a heterogeneous reaction to HONO (Kalberer et al, 1996;Ammann et al, 1998). HONO rapidly photolyzes, thereby producing OH and NO.…”
Section: Chemistry In the Plumementioning
confidence: 99%
“…To carry out experiments with only one 13 NO y species in the gas phase, a series of selective gas traps were used to scrub all but one species from the gas phase, where possible. The traps, which were designed as cylindrical denuders, were coated with Na 2 CO 3 for absorbing HONO or PAN, a mixture of NDA and KOH (1/1) for NO 2 , NaCl for HNO 3 and Co 2 O 3 for NO (see Kalberer et al, 1996Kalberer et al, , 1999. Those denuders, in combination with γ -detectors and the chemiluminescence NO y analyzer, were also used to identify and quantify the various 13 NO y species (Ammann, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…To each trap (the coatings and filter) a separate CsI scintillator crystal with integrated PIN diode was attached (Carroll and Ramsey, USA) which detects the gamma quanta emitted after decay of the 13 N atoms. The detector signal is converted to the flux of the gaseous species into the trap using the inversion procedure reported elsewhere (Guimbaud et al, 2002;Kalberer et al, 1996;Rogak et al, 1991). This flux is proportional to the concentration of the species in the gas phase.…”
Section: Detection Systemmentioning
confidence: 99%